Co‐utilization of secondary aluminum dross and ferronickel slag for preparation of cordierite–mullite insulating ceramic. Issue 3 (18th November 2022) - Liu, Jicheng; Xu, Jiamei; Zhang, Yuanbo; Su, Zijian; Xu, Chenyang; Jiang, Tao
Abstract: Because of the low utilization rate, a large amount of metallurgical slag was piled up or buried each year, resulting in serious environmental pollution and resource waste. This study focused on the value‐add utilization of secondary aluminum dross (SAD) and ferronickel slag (FNS) by preparing porous cordierite–mullite ceramics (CMC) for thermal insulation. The detailed thermodynamic calculation of the preparing process was carried out by using the phase diagram and equilibrium component function module in FactSage 8.1 software, which provided precise theoretical guidance for the practical synthesis experiment. The phase component, microstructure, and mechanical and thermal insulation properties of the prepared CMC at an FNS addition from 5 to 30 wt% were investigated by an X‐ray diffractometer, scanning electron microscopy assembled with an energy‐dispersive spectrometer, and a laser thermal conductivity testing instrument, respectively. It was shown that the original mineral phase of the raw materials applied can be converted to cordierite, mullite, and spinel after sintering at 1350°C, which results in higher strength and lower thermal conductivity of the prepared ceramics. Moreover, the increase of FNS addition promoted the content of cordierite and the microstructure densification of CMC. With the increase of FNS addition, the apparent porosity of CMC decreased from 41.7% to 34.4%, and the average pore size varied from 46.7 to 29.0 μm. The CMC with the lowest thermal conductivity of 0.86 W/(m K) was achieved at 20 wt% of FNS addition, which also had a good compressive strength of 52.8 MPa. The results proved the feasibility of preparing high‐strength thermal insulation ceramics by recycling hazardous metallurgical slag of SAD and FNS, proposing a novel route for high value‐added utilization of industrial solid waste. Abstract : Graphical Abstract: The transformation of main phase in the process of raw material to porous ceramic expressed in crystal structure diagram.